EFEKTIVITAS MODEL PEMBELAJARAN STAD BERBANTUAN CD PEMBELAJARAN DAN CD INTERAKTIF TERHADAP PRESTASI BELAJAR MATEMATIKA - Shinta Dwi Handayani (Universitas Majalengka, 2021)
This study aims to determine the effectiveness of mathematics learning achievement for students who are subjected to the Student Teams Achievement Divisions (STAD) model assisted by Interactive CD, Learning CD and Conventional learning models on flat-shaped materials in grade VII semester II students of SMP Negeri 223 Jakarta. The population in this study were students of class VII SMP Negeri 223 Jakarta. By using cluster random sampling technique selected VII 3 as the control class, VII 7 and VII 8 respectively as the experimental class STAD model assisted by learning CD and STAD model assisted by Interactive CD. The results showed that there was a significant difference between mathematics learning achievement students who are taught by learning using the STAD learning model assisted by Interactive CD, STAD learning model assisted by CD Learning and conventional learning, the learning achievement of students who receive learning using Interactive CD media is better than conventional learning. Likewise, the learning outcomes of students who receive learning using Learning CD media are better than conventional learning. In addition, there is no significant difference between the mathematics learning outcomes of students who are taught using the STAD learning model assisted by Interactive CD and students who use the STAD learning model assisted by the Learning CD.